2010
DOI: 10.1002/lapl.200910154
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Raman spectroscopy for the identification of biofilm formation byStaphylococcus epidermidis

Abstract: Abstract:We report on an investigation into a common problem in microbiology laboratories, which is associated with the difficulty of distinguishing/recognising different strains of the genus Staphylococcus. We demonstrate the potential of Raman spectroscopy as a rapid techniques allowing for the identification of different isolates for the detection of biofilm-positive and biofilm-negative Staphylococcus epidermidis strains. For this, the recorded spectra were interpreted using the approach of principal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…Protein (BSA) solutions were used as standards to compare relative hydration. In this context, Samek et al acquired Raman spectra of the biofilm-forming Staphylococcus epidermidis 1457 strain and its non-biofilm-forming mutant Staphylococcus epidermidis 1457-M10 strain after growth of each on Columbia blood agar culture plates for 24 h [32]. Although there were subtle differences between the spectra of the two strains, the principal component analysis (PCA) of the spectra clearly discriminated the two strains and showed the effects of the biofilm matrix ingredients on the spectra, especially that of polysaccharide inter-cellular adhesions (PIA).…”
Section: Raman Spectroscopy Of Biofilmsmentioning
confidence: 99%
“…Protein (BSA) solutions were used as standards to compare relative hydration. In this context, Samek et al acquired Raman spectra of the biofilm-forming Staphylococcus epidermidis 1457 strain and its non-biofilm-forming mutant Staphylococcus epidermidis 1457-M10 strain after growth of each on Columbia blood agar culture plates for 24 h [32]. Although there were subtle differences between the spectra of the two strains, the principal component analysis (PCA) of the spectra clearly discriminated the two strains and showed the effects of the biofilm matrix ingredients on the spectra, especially that of polysaccharide inter-cellular adhesions (PIA).…”
Section: Raman Spectroscopy Of Biofilmsmentioning
confidence: 99%
“…The investigation of microorganisms [13] as well as the examination of biofilm formations [1,[14][15][16] by using Raman microspectroscopy has currently become quite popular. Components such as DNA, RNA, proteins, lipids, and carbohydrates of the bacterial cells may vary and, therefore, cause the Raman spectra of two different species to be slightly different which can be successfully used for species discrimination [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to extract quantitative information from the experimentally obtained spectral data, we adopted the Rolling Circle Filter (RCF) technique for background removal [1][2][3]. In principle, RCF is a high-pass signal filter that allows separating the narrow Raman spectral peaks from the background whose radius of curvature is significantly higher.…”
Section: Methodsmentioning
confidence: 99%
“…In many applications optical trapping has been combined with Raman microspectroscopy which provides non-invasive spatially resolved mapping of molecular composition of studied sample. Recently, it has been shown that the technique of Raman spectroscopy (including Raman imaging) can be regarded as the method of choice for many studies of microorganisms, cells and biological samples [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%